Cardiac complications of enterovirus rhombencephalitis. Issue 4 (19th March 2004) - Fu, Y C; Chi, C S; Chiu, Y T; Hsu, S L; Hwang, B; Jan, S L; Chen, P Y; Huang, F L; Chang, Y
Abstract : Background: Epidemics of enterovirus 71 infection have caused the death of many children throughout the world. Rhombencephalitis, brain stem encephalitis, and heart failure were present in all of the fatal cases. However, no evidence of myocarditis was noted in the heart specimens, and the mechanism of heart failure remains unknown. Aims: To characterise the presentation of cardiac complications in children with enterovirus rhombencephalitis and discuss its pathogenesis. Methods: Ninety one consecutive patients with enterovirus rhombencephalitis underwent echocardiography. Of these, 17 patients (nine male, eight female; median age 14 months, range 4–57 months) with left ventricular dysfunction were studied. Results: Tachycardia was noted in all patients and systemic hypertension in 12. Muscle-brain fraction of creatine kinase was >5% in 14 patients. Plasma norepinephrine and epinephrine levels were significantly raised in the three patients in whom these were analysed. Electrocardiographic abnormalities were noted in eight patients. Pulmonary oedema was complicated in 15 patients. The initial ejection fraction of the left ventricle was 22–58% (mean 37%, SD 11%). All patients deteriorated to hypotensive shock within 12 hours and 13 died. Heart specimens from seven patients showed no evidence of myocarditis, but significant coagulative myocytolysis, myofibrillar degeneration, and cardiomyocyte apoptosis were observed. Conclusions: Acute heart failure was noted in 19% of patients with enterovirus rhombencephalitis, which had a fatality rate of 77%. It was not caused by myocarditis but possibly by neurogenic cardiac damage.